ANALISA PENENTUAN PARAMETER MEKANIK BATUAN DENGAN METODE RMR DAN GSI PADA KAWASAN PANTAI MELASTI, BALI - I Made Wahyu Pramana; I Wayan Arya (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2020)
In order to do bearing capacity and slope stability analysis of rock, determination of physical and mechanical parameter of the rock is needed. The objective of this study is to determine the mechanical parameter of the rock using RMR and GSI method. Result of this study are rock in Melasti beach area is classified into fair rock with range of GSI value of 35 to 45. Mechanical parameter of the rock using RMR method are f = 25 – 35 and c = 200 KPa – 300 KPa and mechanical parameter using GSI method is f = 24 – 29 and c = 256 KPa – 330 KPa.